MIGRASI TENAGA KERJA PEDESAAN DAN POLA PEMANFAATANNYA - FORCINA SINURAYA, JULIA; -, SAPTANA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Economic development is a dynamic process in medium or long term that brings impact on social economics’ structural change in rural community. The social economic transformation can be as sectoral shiftment or employment, institutional, and norms among wherein community. Macro data assessment shows that sectoral economic shifts faster than employment shiftment. The objective of this paper is to analyze: (1) Macro Employment; (2) Migration scheme of rural labor; (3) Identification activity type in the origin; (4) Driven and apathetic factors of rural labor migration; and (5) The utility scheme of migration in household economy. Macro description (1990 – 2005) on population migration in three representative provinces shows that immigration less than emigration. In general view of that, population move consistently from producer area of agricultural product in the rural to urban area. There two schemes of representative rural migration. Migration scheme in wet land area is seasonal, while one in dry land tends to be constant. The aggregate shows that main driven factor of household member to migrate in two type of agro ecosystem is the limited employment in rural area; in contrary apathetic factors in destination area is higher opportunity of job. Living cost payment is major utility scheme that resulted of household member migration, particularly for household consumption, school fee, house renovation, and saving.
Keywords: Migration, Labor, Rural Area, Utility Scheme.